Double or die : a James Bond adventure / 3. - Higson, Charlie, 1958- (Higson, Charles, 1958- Young Bond, 2009)
Teenage James Bond is on the case when a professor is kidnapped in a north London cemetery, and an encoded letter arrives which, once deciphered, leaves James with just forty-eight hours to rescue the captured scholar and save the world.